Isokinetic strength profiles of elite swimmers - Neophytou, N.; Charalambous, T.; Constantinou, D.; Aginsky, K. (Journal of Sports Science & Medicine, 2012)
Isokinetic strength profiles can assist in determining if elite athletes have enough strength and endurance to complete their required tasks, or whether there are muscle imbalances which could predispose them to injury. There has been very limited research conducted in South Africa on the isokinetic profiles of elite swimmers. The aim of the study was to assess the isokinetic strength and endurance profiles of shoulder internal and external rotator muscles of elite swimmers. Methods: Isokinetic testing was performed on 21 elite swimmers (5 female, 16 male) using a Biodex 3 dynamometer. Strength testing was done using concentrically and eccentrically at 60°/s, completing 5 maximal contractions. Endurance testing was done at 180°/s, completing 15 maximal contractions. Swimmers with acute injuries were excluded from the study. Muscular endurance was measured using the relative fatigue ratio, and muscular strength with various strength ratios as well as average power, and maximum repetition total work. The strength ratios measured included torque to body ratio, the reciprocal ratio, the functional ratio and bilateral ratio. Statistical analysis included mean and standard deviation for strength and endurance. An isokinetic strength profile was determined for elite swimmers in a South African context. Results: The main findings for strength included a bilateral discrepancy between the arms of less than 10% for both the internal and external rotator muscles in both female and male swimmers, except in the ECC/ECC (eccentric/ eccentric) test at 60°/s where the external rotators had a discrepancy of 17.8% in the female swimmers. Both male and female swimmers showed a better than average peak torque to body weight ratio between the limbs as compared to non-elite athletes. With respect to endurance, the relative ration of the internal rotators of female swimmers ranged from 8.76 - 9.0% and the external rotators ranged from 18.1-25.9% and for the male swimmers the internal rotators ranged from 6.2 - 9.1% and the external rotators ranged from 16.4 - 17.6%. Conclusions: Swimmer external rotator muscles fatigued at a quicker rate than the internal rotators for both male and female swimmers tested. When compared to international data, strength and endurance profiles of elite South African swimmers were not comparable to those found internationally. Further research should focus on analysing the possible relationship between strength and endurance adaptations, and the development of specific injuries. This would contribute to determining the potential risk for injury due to muscle strength and endurance adaptations, and possible individual rehabilitation interventions for injury prevention.